2023
DOI: 10.1093/ejendo/lvad139
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors, and optimal way to determine overweight, obesity, and morbid obesity in the first Dutch cohort of 2338 long-term survivors of childhood cancer: a DCCSS-LATER study

Vincent G Pluimakers,
Jenneke E van Atteveld,
Demi T C de Winter
et al.

Abstract: BACKGROUND Overweight and obesity are common challenges among childhood cancer survivors. Overweight may be disguised, as survivors can have normal weight but high fat percentage (fat%) on dual-energy X-ray absorptiometry (DXA). We aimed to assess prevalence, identify determinants and biomarkers and assess which method captures overweight best, in a nationwide cohort. METHODS Prevalence of overweight and obesity, primarily de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“… 10 The prevalence of clinically ascertained obesity among survivors of childhood cancer in their 30s ranges from 13.5% in a Dutch cohort compared to 15.1% in the general Dutch population to 36% in a North American cohort compared to 31.6% in the age-, sex-, and race-matched general U.S. population. 11 , 12 Importantly, BMI does not account for the imbalance between lean and fat mass distribution, and a number of studies have highlighted treatment-related changes in body composition among survivors. They observed that 42% to 46% of male and >50% of female survivors were misclassified as nonobese based on BMI compared to body fat percentage (obesity defined as body fat percentage ≥25% for males and ≥30% for females) by dual X-ray absorptiometry (DXA) measurements.…”
Section: Obesitymentioning
confidence: 99%
“… 10 The prevalence of clinically ascertained obesity among survivors of childhood cancer in their 30s ranges from 13.5% in a Dutch cohort compared to 15.1% in the general Dutch population to 36% in a North American cohort compared to 31.6% in the age-, sex-, and race-matched general U.S. population. 11 , 12 Importantly, BMI does not account for the imbalance between lean and fat mass distribution, and a number of studies have highlighted treatment-related changes in body composition among survivors. They observed that 42% to 46% of male and >50% of female survivors were misclassified as nonobese based on BMI compared to body fat percentage (obesity defined as body fat percentage ≥25% for males and ≥30% for females) by dual X-ray absorptiometry (DXA) measurements.…”
Section: Obesitymentioning
confidence: 99%